A Mass‐Spectrometry‐Based Approach to Distinguish Annular and Specific Lipid Binding to Membrane Proteins. Issue 9 (29th January 2020) - Bolla, Jani Reddy; Corey, Robin A.; Sahin, Cagla; Gault, Joseph; Hummer, Alissa; Hopper, Jonathan T. S.; Lane, David P.; Drew, David; Allison, Timothy M.; Stansfeld, Phillip J.; Robinson, Carol V.; Landreh, Michael
Abstract: Membrane proteins engage in a variety of contacts with their surrounding lipids, but distinguishing between specifically bound lipids, and non‐specific, annular interactions is a challenging problem. Applying native mass spectrometry to three membrane protein complexes with different lipid‐binding properties, we explore the ability of detergents to compete with lipids bound in different environments. We show that lipids in annular positions on the presenilin homologue protease are subject to constant exchange with detergent. By contrast, detergent‐resistant lipids bound at the dimer interface in the leucine transporter show decreased koff rates in molecular dynamics simulations. Turning to the lipid flippase MurJ, we find that addition of the natural substrate lipid‐II results in the formation of a 1:1 protein–lipid complex, where the lipid cannot be displaced by detergent from the highly protected active site. In summary, we distinguish annular from non‐annular lipids based on their exchange rates in solution. Abstract : Separating the wheat from the chaff : Distinguishing specific and non‐specific lipid binding to membrane proteins is a major challenge. Non‐annular lipid interactions can be identified using a detergent competition assay and native mass spectrometry (MS). MD simulations reveal the location of specific lipid‐binding sites with slow k off rates, confirming the MS data.